Assessment of Genetic Variability for Yield, Yield Attributing and Quality Traits of Promising Genotypes of Cluster Bean [Cyamopsis tetragonaloba L. Taub.] - Teja, Rachamalla Ravi; Saidaiah, P.; Kumar, A. Kiran; Bhasker, K.; Geetha, A. (International Journal of Bio-resource and Stress Management, 2023)
The present study was conducted to evaluate twenty four (24) genotypes along with 1 check variety (Pusa Navbahar) of cluster bean during kharif, July–September, 2019 at College of Horticulture, Rajendranagar, Sri Konda Laxman Telangana State Horticultural University, Telangana, India to estimate variability, broad sense heritability and genetic advance for pod yield and yield attributing traits. The observations were recorded on various growth, yield and quality parameters. High estimates of GCV and PCV were recorded for plant height, number of branches plant-1, pod length, pod weight and number of pods plant-1. Protein content, gum content and fibre content recorded moderate to high PCV and GCV. High heritability coupled with high genetic advance as % of mean was observed for plant height, number of branches plant-1, number of clusters plant-1, days to maturity, number of pods plant-1, pod length, pod girth, pod weight, number of seeds pod-1, pod yield plant-1, pod yield ha-1, protein content, gum content and fibre content. High variability in conjunction with high genetic advance as % of mean indicating the predominance of additive gene action. These traits could be exploited through manifestation of dominance and epistatic components through heterosis breeding. The overall assessment showed that there was wide variability among cluster bean genotypes which has important implication for selection of cluster bean genotypes for yield and quality attributes.